Corporate social responsibility, sustainability and ethical public relations : strengthening synergies with human resources - Pompper, Donnalyn, 1960- (Changing context of managing people., 2018)
This book offers practical advice for building organizations with social responsibility and sustainability organically built in - based on two-way communication between human resources (HR) and public relations (PR) departments working together as an organizational conscience touchstone benefiting People, Planet, and Profit.